Changes in the accumulated oxygen deficit and energy cost of running 400 metres - Machado Reis, V.; Paixão Miguel, P. (New Studies in Athletics, 2007)
The aim of this study was to compare the accumulated oxygen deficit (AOD), the energy cost of running and the anaerobic fraction of energy elicited during all-out 400 m track runs in the off-season and summer preparation phases of a season. Five trained 400m runners with an average best time of 47.72 took part in the tests. The authors found that the subjects` performance improved significantly between the two tests but this improvement was not matched by significant changes in the AOD. They did find that the performance improvement was matched by significant decreases in the energy cost of running and oxygen uptake during the run and a significant increase in the anaerobic fraction of energy used. These results suggest that improving high-speed running economy is a key to better performance in the 400m.